A Hairy Cell Leukaemia Variant – A Rare Case Report - Pande, Pankaj (JCDR Research and Publications (P) Limited, 2013)
The aim of the article is to present a rare case of Hairy cell leukaemia variant (HCl-V) which is a distinct clinico-pathological entity with intermediate features between classical HCl (HCl-C) and B-cell prolymphocytic leukaemia. It is an uncommon disorder accounting for approximately 0.4% of chronic lymphoid malignancies and 10% of all HCl cases. A 58 year old woman presented with pain abdomen and loss of weight. On examination she had massive splenomegaly. Peripheral smear was reported as chronic lymphoproliferative disorder (? Hairy cell leukemia or splenic lymphoma with villous lymphocytes). On Bone marrow examination, differential diagnosis was given as splenic lymphoma with villous lymphocytes (SLVL) and prolymphocytic variant of Hairy cell leukemia. On flow cytometric analysis, these cells were positive for CD11c, CD19, CD20, and CD22. Based on the clinical, peripheral smear, bone marrow and flow cytometry findings, a diagnosis of hairy cell leukaemia variant was confirmed. The differential diagnosis should always include SLVL, HCL-C and Japanese variant HCL because they have different clinical and biological features, particularly regarding their response to purine analogue-based treatment or splenectomy.